2020
DOI: 10.1093/heapro/daaa031
|View full text |Cite
|
Sign up to set email alerts
|

Engaging citizen scientists to build healthy park environments in Colombia

Abstract: Colombia’s Recreovía program offers community-based free physical activity (PA) classes in parks. We evaluated built and social environmental factors influencing Recreovía local park environments, and facilitated a consensus-building and advocacy process among community members, policymakers and academic researchers aimed at improving uptake and impact of the Recreovía program. We used a mixed-methods approach, with individual and contextual PA measurements and a resident-enabled participatory approach (the Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 40 publications
(58 reference statements)
3
28
0
1
Order By: Relevance
“…Our results could reinforce interventions of socially transmitted healthy habits among stakeholders and participants as they show the potential of online social networks to provide a greater understanding of the community dynamics of physical activity programs ( Ferrer & Ellis, 2017 ; Rubio et al, 2020 ). This work serves as an example of an interdisciplinary systemic approach for promoting social and health dimensions of a community-based intervention occurring in parks in a low- to middle-income country.…”
Section: Discussionsupporting
confidence: 58%
“…Our results could reinforce interventions of socially transmitted healthy habits among stakeholders and participants as they show the potential of online social networks to provide a greater understanding of the community dynamics of physical activity programs ( Ferrer & Ellis, 2017 ; Rubio et al, 2020 ). This work serves as an example of an interdisciplinary systemic approach for promoting social and health dimensions of a community-based intervention occurring in parks in a low- to middle-income country.…”
Section: Discussionsupporting
confidence: 58%
“…Our study of frequent recreational and commuter users of a metropolitan park in St. Louis demonstrated that Our Voice is a feasible and effective method for assessing drivers of access and use of large metropolitan parks. The similarity in findings across seemingly different user groups (recreational users and commuters) reinforces the richness of the Our Voice method, in which a small number of citizen scientists from a given community (in this case, frequent park users) can provide sufficient information about that community's overall experience, needs, and priorities (Rosas et al, 2016;Rubio et al, 2021). This makes Our Voice a powerful method for assessing largescale community amenities like major metropolitan parks, which serve millions of people per year and whose service areas are geographically large and demographically diverse.…”
Section: Discussionmentioning
confidence: 74%
“…The results also showed that the studied population in La Guajira complieds with the recommended physical activity, which could be a contributing factor to the prevention of pathologies associated to cardiovascular diseases and type 2 diabetes ( 2 , 40 , 43 ). Further to this, proposed population strategies, that include the creation of bio-health spaces with mechanical elements that facilitate physical activity, have been made with the aim to encourage an increase in physical activity ( 45 ). However, these strategies are not options for all the ethnic groups and are instead specifically designed for the Indigenous.…”
Section: Discussionmentioning
confidence: 99%